Kv7 channels are upregulated during striatal neuron development and promote maturation of human iPSC-derived neurons - Telezhkin, Vsevolod (Pflugers Arch, 2018)
Kv7 channels determine the resting membrane potential of neurons and regulate their excitability. Even though dysfunction of Kv7 channels has been linked to several debilitating childhood neuronal disorders, the ontogeny of the constituent genes, which encode Kv7 channels (KNCQ), and expression of their subunits have been largely unexplored. Here, we show that developmentally regulated expression of specific KCNQ mRNA and Kv7 channel subunits in mouse and human striatum is crucial to the functional maturation of mouse striatal neurons and human-induced pluripotent stem cell-derived neurons. This demonstrates their pivotal role in normal development and maturation, the knowledge of which can now be harnessed to synchronise and accelerate neuronal differentiation of stem cell-derived neurons, enhancing their utility for disease modelling and drug discovery.